2009
DOI: 10.1073/pnas.0811058106
|View full text |Cite
|
Sign up to set email alerts
|

A family of Salmonella virulence factors functions as a distinct class of autoregulated E3 ubiquitin ligases

Abstract: Processes as diverse as receptor binding and signaling, cytoskeletal dynamics, and programmed cell death are manipulated by mimics of host proteins encoded by pathogenic bacteria. We show here that the Salmonella virulence factor SspH2 belongs to a growing class of bacterial effector proteins that harness and subvert the eukaryotic ubiquitination pathway. This virulence protein possesses ubiquitination activity that depends on a conserved cysteine residue. A crystal structure of SspH2 reveals a canonical leuci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
223
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(229 citation statements)
references
References 35 publications
5
223
1
Order By: Relevance
“…In both copies of the NEL domain there was no visible electron density for loop αM-αN (residues 709-728) of the C-terminal helix bundle. In contrast, the loop linking the LRR and NEL domains that was disordered in the published apo structures of IpaH3 [21] and SspH2 [22] is clearly defined in the Trx1 bound SlrP structure. The catalytic loop carrying the conserved C 546 XD 548 motif [24] is exposed to the solvent and accessible to the E2-Ub conjugate.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…In both copies of the NEL domain there was no visible electron density for loop αM-αN (residues 709-728) of the C-terminal helix bundle. In contrast, the loop linking the LRR and NEL domains that was disordered in the published apo structures of IpaH3 [21] and SspH2 [22] is clearly defined in the Trx1 bound SlrP structure. The catalytic loop carrying the conserved C 546 XD 548 motif [24] is exposed to the solvent and accessible to the E2-Ub conjugate.…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies demonstrated that removal of the LRR domain of SlrP (residues 1-457) resulted in dramatic increase of its ubiquitin E3 ligase activity [22]. These results suggest that the LRR domain, known as a versatile structural framework for protein-protein interaction [47], is not implicated in substrate binding but is rather involved in the regulation of the adjacent NEL catalytic domain [14].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations